ANALISIS COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN OBJEK WISATA MUSEUM KOTA LAMA SEMARANG - Ifaf Agasinta, Ismah; Subowo, Ari; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2024)
Semarang city is one of the cities that has great potential in the tourism sector. Various types of tourism are offered, one of which is cultural and historical tourism. Semarang Old City Museum is one of the historical tourist destinations in Semarang City. The development of the Semarang Old City Museum is still said to have not gone well allegedly because the collaboration between the government, the private sector, and the community has not been optimal. This research aims to describe the stages of the collaborative governance process and the factors that influence the collaborative governance process in the development of the Semarang Old City Museum attraction. In this study, researchers used qualitative research methods with data collection techniques through interviews, observations, and documentations. The results of this study indicate that the collaborative governance process in the development of the Semarang Old City Museum can be said to be sufficient because the five stages of the collaborative process still have aspects that need to be improved and there are three factors that have not gone well, namely membership, communication, and resource factors. The researcher provides suggestions to improve the collaborative process and improve communication and collaboration resources so that the development of the Semarang Old City Museum can run optimally.